Aortic 4D flow: Quantification of signal‐to‐noise ratio as a function of field strength and contrast enhancement for 1.5T, 3T, and 7T. Issue 5 (16th June 2014) - Hess, Aaron T.; Bissell, Malenka M.; Ntusi, Ntobeko A.B.; Lewis, Andrew J.M.; Tunnicliffe, Elizabeth M.; Greiser, Andreas; Stalder, Aurelien F.; Francis, Jane M.; Myerson, Saul G.; Neubauer, Stefan; Robson, Matthew D.
Abstract : Purpose: To investigate for the first time the feasibility of aortic four‐dimensional (4D) flow at 7T, both contrast enhanced (CE) and non‐CE. To quantify the signal‐to‐noise ratio (SNR) in aortic 4D flow as a function of field strength and CE with gadobenate dimeglumine (MultiHance). Methods: Six healthy male volunteers were scanned at 1.5T, 3T, and 7T with both non‐CE and CE acquisitions. Temporal SNR was calculated. Flip angle optimization for CE 4D flow was carried out using Bloch simulations that were validated against in vivo measurements. Results: The 7T provided 2.2 times the SNR of 3T while 3T provided 1.7 times the SNR of 1.5T in non‐CE acquisitions in the descending aorta. The SNR gains achieved by CE were 1.8‐fold at 1.5T, 1.7‐fold at 3T, and 1.4‐fold at 7T, respectively. Conclusion: The 7T provides a new tool to explore aortic 4D flow, yielding higher SNR that can be used to push the boundaries of acceleration and resolution. Field strength and contrast enhancement at all fields provide significant improvements in SNR. Magn Reson Med 73:1864–1871, 2015. © 2014 Wiley Periodicals, Inc.